Five new genera of angle-wing katydids (Orthoptera: Tettigoniidae: Phaneropterinae: Microcentrini) from the Amazon Rainforest - de Mello Mendes, Diego Matheus; Chamorro-Rengifo, Juliana; Rafael, José Albertino (Zootaxa, 2020)
Microcentrini Brunner von Wattenwyl, 1878 is within the subfamily Phaneropterinae and currently comprises 11 genera and 81 species with Neotropical distribution. In this paper, five new genera are described: Boroseiyla gen. nov. (type species Boroseiyla tupeba sp. nov.), Caauara gen. nov. (type species Caauara pinima sp. nov.), Capiguara gen. nov. (type species Capiguara trimaculata sp. nov.), Hyalipenna gen. nov. (type species Hyalipenna tetralineata sp. nov.) and Tuaia gen. nov. (type species Tuaia panacarica sp. nov.) covering a total of seventeen new species registered for the Amazon rainforest. Moreover, Microcentrum nigrolineatum is included in Boroseiyla gen. nov. (Boroseiyla nigrolineatus comb. nov.). Keys to the species of the described genera, maps and observations of natural history are provided.